Pengaruh Impulsivitas dan Media Komunikasi terhadap Perbedaan Partisipasi Diskusi Online - Irma Suhartini; Fathul Himam (Faculty of Psychology, Universitas Gadjah Mada, 2018)
This study aims to determine the effect of impulsivity and computer-mediated communication on differences in online participation. This research is an experimental research with Posttest only design. Participants involved in this study were students with an age range of 17-22 years, totaling 30 participants. Participants will be divided into two groups namely using the computer-mediated communication real name (CMR) and computer-mediated communication anonymously (CMA), each group consists of 15 participants. This study used Barrat Impulsive Scale (BIS) 11 to determine participants' impulsivity. Data analysis in this study used Two-way analysis of variance. Based on the result of the interaction model analysis between impulsivity and computer-mediated communication to online participation, it is known that the value of F = 1,587 with significance equal to 0,219 (p> 0,05). This research found that there is no significant difference in online participation based on computer-mediated communication of CMR and CMA, both at low, medium and high levels of impulsivity.